Second Harmonic Generation Imaging of Collagen in Chronically Implantable Electrodes in Brain Tissue - Esquibel, Corinne R.; Wendt, Kristy D.; Lee, Heui C.; Gaire, Janak; Shoffstall, Andrew; Urdaneta, Morgan E.; Chacko, Jenu V.; Brodnick, Sarah K.; Otto, Kevin J.; Capadona, Jeffrey R.; Williams, Justin C.; Eliceiri, K. W. (Frontiers in Neuroscience, 2020)
Advances in neural engineering have brought about a number of implantable devices for improved brain stimulation and recording. Unfortunately, many of these micro-implants have not been adopted due to issues of signal loss, deterioration, and host response to the device. While glial scar characterization is critical to better understand the mechanisms that affect device functionality or tissue viability, analysis is frequently hindered by immunohistochemical tissue processing methods that result in device shattering and tissue tearing artifacts. Devices are commonly removed prior to sectioning, which can itself disturb the quality of the study. In this methods implementation study, we use the label free, optical sectioning method of second harmonic generation (SHG) to examine brain slices of various implanted intracortical electrodes and demonstrate collagen fiber distribution not found in normal brain tissue. SHG can easily be used in conjunction with multiphoton microscopy to allow direct intrinsic visualization of collagen-containing glial scars on the surface of cortically implanted electrode probes without imposing the physical strain of tissue sectioning methods required for other high resolution light microscopy modalities. Identification and future measurements of these collagen fibers may be useful in predicting host immune response and device signal fidelity.